Chiese cristiane cinesi e Covid-19 tra confinamenti, percezione del rischio e discriminazioni in Italia durante il lockdown - Castaldo, Miriam (Antropologia Pubblica, 2024)
Throughout the month of June 2020, a short online ethnographic study was carried out within theMedical Anthropology Service, National Institute for Health, Migration and Poverty (NIHMP). Through a structured interview, an attempt was made to explore the social, economic and health effects of Covid-19 on the lives of a group of 36 Chinese people, who are seeking international protection in Italy because they are Evangelical Christians members of proscribed domestic churches in China. From the interviews, strategies of the "home" Christian faith profession emerged and appeared heterogeneously protective towards the pandemic.